2011
DOI: 10.1007/s00068-010-0068-z
|View full text |Cite
|
Sign up to set email alerts
|

Lung tissue apoptosis in abdominal hypertension

Abstract: The available findings suggest that intra-abdominal pressure greater than 15 mmHg could irreversibly damage pulmonary cells and both coagulation necrosis parameters and the number of apoptosis increase in accordance with the pressure level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(41 reference statements)
0
1
1
Order By: Relevance
“…It means that CO 2 pneumoperitoneum in higher pressures have lethal effects on kidney tubular cells. Generally, apoptotic pathways were activated by p53 expression in our before studies [10][11][12][13][14].However, in this study, we detected that p53 expression was detected only 20 mmHg applied groups. This protection might be related with mechanical resistance of renal capsule and also retroperitoneal location of kidneys.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…It means that CO 2 pneumoperitoneum in higher pressures have lethal effects on kidney tubular cells. Generally, apoptotic pathways were activated by p53 expression in our before studies [10][11][12][13][14].However, in this study, we detected that p53 expression was detected only 20 mmHg applied groups. This protection might be related with mechanical resistance of renal capsule and also retroperitoneal location of kidneys.…”
Section: Discussioncontrasting
confidence: 82%
“…However, it was revealed that the side effects of CO 2 pneumoperitoneum such as organ ischemia, cell death, physiopathological changes were minimal and reversible without any apparent sequel when the shorter time and lower pressure was used. Because we have studied the effects of CO 2 pneumoperitoneum in different intraabdominal organs in our different studies before [10][11][12][13][14], we have standardized CO 2 pressure for experimental studies.…”
Section: Discussionmentioning
confidence: 99%